2021
DOI: 10.1016/j.cortex.2021.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping but distinct: Distal connectivity dissociates hand and tool processing networks

Abstract: The processes and organizational principles of information involved in object recognition have been a subject of intense debate. These research efforts led to the understanding that local computations and feedforward/feedback connections are essential to our representations and their organization. Recent data, however, has demonstrated that distal computations also play a role in how information is locally processed. Here we focus on how long-range connectivity and local functional organization of information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 99 publications
(147 reference statements)
3
19
0
Order By: Relevance
“…Previous evidence shows that distal functional connectivity is correlated with task-based activation in OTC ( Chen et al, 2017 ; Amaral et al, 2021 ). It is therefore possible that most-connected voxels are effectively the same as those showing strongest local activation, and therefore most-connected and most-activated voxel sets might yield equivalent decoding performance.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous evidence shows that distal functional connectivity is correlated with task-based activation in OTC ( Chen et al, 2017 ; Amaral et al, 2021 ). It is therefore possible that most-connected voxels are effectively the same as those showing strongest local activation, and therefore most-connected and most-activated voxel sets might yield equivalent decoding performance.…”
Section: Resultsmentioning
confidence: 95%
“…Indeed, connectivity is a major constraint on the functional organization of cerebral cortex in general, such that the functional response of a given region is partially determined by the integration of relevant information shared via structural and functional connectivity to other brain regions (e.g., Garcea et al, 2019 ; Lee et al, 2019 ; Mahon and Caramazza, 2011 ; Sporns and Zwi, 2004 ; Sporns, 2014 ). More specifically, category-preferring OTC responses are functionally coupled with, and modulated by, distal regions that share the same category preference (e.g., tool responses in medial fusiform gyrus (MFus) are shaped by inferior parietal cortex; Amaral et al, 2021 ; Chen et al, 2017 ; Garcea et al, 2019 ; Lee et al, 2019 ); similarly, OTC responses for multiple visual categories (e.g., faces, objects, bodies, and places) can be reliably predicted from patterns of white matter connectivity to the wider brain ( Saygin et al, 2012 , 2016 ; Osher et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This intimate link between tools and hands is reflected in the neural and cognitive overlap between how tools and hands are processed (e.g. 15 17 ). Some experiments show that hand grasping might be automatically prepared in the presence of graspable tools.…”
Section: Discussionmentioning
confidence: 99%
“…This sequential preparation of eye and hand programs in tool recognition is reflected in distinct organization of the neural pathways processing visual information about tools. It has been shown that the recognition of manipulable objects is achieved through interactions between the dorsal and ventral streams within the tool processing network 1 , 3 , 17 , 35 38 . Handles are usually recognized by their elongated but coarse shape, which does not require the processing of fine spatial details, as grasping usually entails a coarse preshaping of the hand 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation